2018
DOI: 10.1136/bjophthalmol-2018-312072
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, prospective clinical trial of platelet-rich plasma injection in the management of severe dry eye

Abstract: NCT02257957.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…In vitro and clinical studies have investigated the applicability of PRP as a therapeutic agent in nerve injuries [24], myocardial infarction [25], cosmetic surgery [26,27] and eye disease [28]. Furthermore, PRP has been increasingly utilized in sports medicine to treat ligament and tendon lesions due to its association with shortened recovery times and improved functional outcomes, but there is a paucity of good-quality scientific evidence demonstrating its effectiveness [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and clinical studies have investigated the applicability of PRP as a therapeutic agent in nerve injuries [24], myocardial infarction [25], cosmetic surgery [26,27] and eye disease [28]. Furthermore, PRP has been increasingly utilized in sports medicine to treat ligament and tendon lesions due to its association with shortened recovery times and improved functional outcomes, but there is a paucity of good-quality scientific evidence demonstrating its effectiveness [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that PRP improved patients' symptoms significantly. It was also reported that the tear volume was increased after the injection of PRP [52]. Acceleration and improvement of tissue regeneration are caused by growth factors released from the platelets [67].…”
Section: Growth Factor Deliverymentioning
confidence: 95%
“…Among all studies treating dry eye diseases (DED), Avila et al 27 was designated at clinical evidence level II, and Garcia-Conca et al 28 at clinical level III. Both studies included a comparison group and used PRP eye drops.…”
Section: Primary and Secondary Dry Eye Diseasesmentioning
confidence: 99%